Penerapan Bauran Pemasaran Pada Ud Uni Timber - Suryani Suryani (Universitas Internasional Batam, 2021)
The business owner has been managing a selling wood business since 2001. By running a business for years, the owner has a lot of experience in the techiques of marketing products. As science advances and technology changes, there are many methods that shop owners can use to help increase their business. However, the owner of the UD Uni Timber still persisted with the old sales method, this situation caused the business that was started by the owner to lose in competition. The method used is designing a promotional program. The promotional mix that is applied is the implementation of advertisements, individual sales, and sales promotions. The results of the author’s implementation of the marketing mix at UD Uni Timber are creating Instagram account, personal selling and giving discounts for UD Uni Timber Customers.